2014
DOI: 10.1161/circinterventions.113.000926
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Instantaneous Wave-Free Ratio as a Pressure-Only Estimation of Underlying Coronary Flow Reserve

Abstract: Background— Coronary flow reserve has extensive validation as a prognostic marker in coronary disease. Although pressure-only fractional flow reserve (FFR) improves outcomes compared with angiography when guiding percutaneous coronary intervention, it disagrees with coronary flow reserve classification 30% of the time. We evaluated whether baseline instantaneous wave-free ratio (iFR) could provide an improved pressure-only estimation of underlying coronary flow reserve. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
60
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 157 publications
(62 citation statements)
references
References 50 publications
1
60
1
Order By: Relevance
“…Multiple studies presented approaches to avoid hyperemia for physiological lesion assessment, such as instantaneous wave‐free ratio and resting distal pressure/aortic pressure measurements. The resting indices perform similar with an overall diagnostic agreement between 80% and 90% when compared with FFR depending on distribution of lesions included in the studies 20, 21, 22, 23, 24. Still, instantaneous wave‐free ratio–based strategies versus an FFR strategy resulted in comparable clinical outcomes at 1 year in 2 large, randomized clinical trials 23, 24.…”
Section: Discussionmentioning
confidence: 71%
“…Multiple studies presented approaches to avoid hyperemia for physiological lesion assessment, such as instantaneous wave‐free ratio and resting distal pressure/aortic pressure measurements. The resting indices perform similar with an overall diagnostic agreement between 80% and 90% when compared with FFR depending on distribution of lesions included in the studies 20, 21, 22, 23, 24. Still, instantaneous wave‐free ratio–based strategies versus an FFR strategy resulted in comparable clinical outcomes at 1 year in 2 large, randomized clinical trials 23, 24.…”
Section: Discussionmentioning
confidence: 71%
“…In the JUSTIFY-CFR study (Joined Coronary Pressure and Flow Analysis to Determine Diagnostic Characteristics of Basal and Hyperemic Indices of Functional Lesion Severity-Coronary Flow Reserve), iFR had better agreement with coronary flow reserve than did FFR. 5 Also, FFR was found to be more likely to overestimate lesion severity than iFR, most likely because hyperemia causes a pressure drop below the FFR threshold of 0.80 in lesions of interme- 18,19 Thus, the FFR threshold that was used in our trial may not have been optimal, although it was the threshold used in the FAME (Fractional Flow Reserve Versus Angiography for Multivessel Evaluation) and FAME 2 trials. 2,3 The proportion of evaluated lesions that were hemodynamically important was low in both groups.…”
Section: Discussionmentioning
confidence: 89%
“…[4][5][6][7] The instantaneous wave-free ratio (iFR) is a recently developed physiological index used to assess the severity of stenosis.The iFR is calculated by measuring the resting pressure gradient across a coronary lesion during the portion of diastole when microvascular resistance is low and stable. 8 Benefits of iFR include the ability to obtain an instantaneous lesion assessment without the need to administer a hyperemic agent, such as adenosine.…”
mentioning
confidence: 99%
“…Our trial also provides clinical evidence that there is no significant advantage to the administration of a hyperemic agent -a finding consistent with results of studies in which iFR and FFR were compared with other reference standards. 13,14,19,20 Although evidence supporting the benefits of physiologically guided revascularization has accumulated over the past decade, adoption of this approach in clinical practice has lagged. There are many reasons for this, including equipment and drug costs, inadequate reimbursement, physician preferences, patient symptoms, and addi- …”
Section: Discussionmentioning
confidence: 99%
“…11 Several studies have questioned the need for the administration of a vasodilator to assess stenosis severity. [12][13][14] In these studies, investigators found that in determining stenosis severity, FFR was not superior to the instantaneous wave-free ratio (iFR), a pressurederived index of stenosis severity that is not obtained with the administration of a vasodilator. We aimed to determine the efficacy and safety of an iFR-guided strategy versus an FFR-guided strategy for coronary revascularization.…”
mentioning
confidence: 99%